An Examination of Gender Differences in the Association of Adolescent Substance use with Eating and Weight Loss Attitudes. (10th November 2018) - Thomas, Rebekah L.; Kelly, Adrian B.; Chan, Gary C. K.; Hides, Leanne M.; Quinn, Catherine A.; Kavanagh, David J.; Williams, Joanne W.
ABSTRACT: Objective : To assess gender differences in the relationship between eating and weight loss attitudes (EWAs), and 30-day tobacco and alcohol use among adolescents, while controlling for potential confounds (age, country of birth, psychological distress, pubertal development, peer alcohol and tobacco use, and sexual activity). Methods : School students aged between 11 and 17 years ( N = 10, 273) from high schools in the State of Victoria (Australia) completed surveys in class under conditions of anonymity and confidentiality. Results : The interaction between EWAs and gender was significant for tobacco use but not for alcohol use, indicating that the effect of EWAs on tobacco use, but not alcohol use, vary by gender. Conclusions : Tobacco use was related to EWAs in adolescent females but not males, and this is consistent with the possibility that females use tobacco in an instrumental fashion to control weight. Implications and Contribution : Female adolescents high in eating and weight loss attitudes were more likely to engage in tobacco use. In contrast, eating and weight loss attitudes were not related to male tobacco use. These results point to the potential importance of developing gender-specific approaches towards addressing problematic behaviors in adolescent populations.